Mineral Element Analyses of Switchgrass Biomass: Comparison of the Accuracy and Precision of Laboratories. (1st March 2017) - Vogel, Kenneth P.; Medill, Rose; Masterson, Steven D.; Mitchell, Robert B.; Sarath, Gautam
Abstract : Core Ideas: Mineral concentration of plant biomass can affect its use in thermal conversion to energy. Precision and accuracy of laboratory mineral analyses of plant biomass can vary significantly. Standard samples need to be used to monitor laboratories precision and accuracy. Mineral concentration of plant biomass can affect its use in thermal conversion to energy. The objective of this study was to compare the precision and accuracy of university and private laboratories that conduct mineral analyses of plant biomass on a fee basis. Accuracy and precision of the laboratories was tested by having all laboratories conduct mineral analyses on subsamples of the same set of standard switchgrass ( Panicum virgatum L.) samples and a certified standard. Laboratories differed significantly in both accuracy and precision even though several used the same analysis method indicating that the differences among laboratories were due to within laboratory procedures and quality control. Laboratories should be using sample standards to monitor both precision and accuracy of their mineral analyses. It would be advisable for researchers submitting samples to service laboratories to replicate the unknown samples to determine precision and to include replicated standards among the submitted samples to determine accuracy.